2020
DOI: 10.1001/jama.2019.22176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin C, Hydrocortisone, and Thiamine vs Hydrocortisone Alone on Time Alive and Free of Vasopressor Support Among Patients With Septic Shock

Abstract: It is unclear whether vitamin C, hydrocortisone, and thiamine are more effective than hydrocortisone alone in expediting resolution of septic shock.OBJECTIVE To determine whether the combination of vitamin C, hydrocortisone, and thiamine, compared with hydrocortisone alone, improves the duration of time alive and free of vasopressor administration in patients with septic shock. DESIGN, SETTING, AND PARTICIPANTSMulticenter, open-label, randomized clinical trial conducted in 10 intensive care units in Australia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
512
4
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(555 citation statements)
references
References 28 publications
13
512
4
4
Order By: Relevance
“…8 Similarly, the VITAMINS trial showed that a combination of IV vitamin C, hydrocortisone, and thiamine did not improve duration of time alive or free from vasopressor administration compared with hydrocortisone alone in a population with septic shock. 9 Physicians from China have stated on various media outlets that they have successfully treated more than 50 patients with moderate to severe COVID-19 with large doses of IV vitamin C (10 000-20 000 mg/d), leading to a shorter mean hospital length of stay compared with untreated patients with COVID-19 and no incidences of death. 10 Details of this evidence are unavailable because these findings have not (at the time of this writing) been published in either preprint or peer-reviewed journals.…”
Section: Vitamin Cmentioning
confidence: 99%
“…8 Similarly, the VITAMINS trial showed that a combination of IV vitamin C, hydrocortisone, and thiamine did not improve duration of time alive or free from vasopressor administration compared with hydrocortisone alone in a population with septic shock. 9 Physicians from China have stated on various media outlets that they have successfully treated more than 50 patients with moderate to severe COVID-19 with large doses of IV vitamin C (10 000-20 000 mg/d), leading to a shorter mean hospital length of stay compared with untreated patients with COVID-19 and no incidences of death. 10 Details of this evidence are unavailable because these findings have not (at the time of this writing) been published in either preprint or peer-reviewed journals.…”
Section: Vitamin Cmentioning
confidence: 99%
“…However, in a recent prospective case series exploring high-dose intravenous vitamin C (15-100 g) administration, increased vitamin C intake was not associated with any cases of symptomatic renal stones and kidney injury [34]. Moreover, significant side effects of vitamin C are not reported in any of the mentioned controlled trials, including the most recent VITAMIN randomized trial [35].…”
Section: Discussionmentioning
confidence: 98%
“…Since the publication of the retrospective before and after study by Dr. Marik and colleagues, in which administration of hydrocortisone, intravenous (IV) vitamin C, and thiamine was indicated to provide a survival advantage in septic patients [1], there has been a prevalence of clinical trials of variable quality and subsequent meta-analyses indicating variable outcomes [2]. Unlike previous combination trials, which did not control for corticosteroid use in the control arm, the recently published VITAMINS randomized clinical trial standardized corticosteroid administration in the control arm to determine if IV vitamin C and thiamine could provide an additional survival advantage over hydrocortisone alone [3]. This trial showed no benefit of the combination of hydrocortisone, IV vitamin C, and thiamine in comparison to hydrocortisone alone.…”
Section: Is the Vitamins Rct Indicating Potential Redundancy Betweenmentioning
confidence: 99%